Nursing Faculty Resilience During a Time of Disruption and Change. Issue 5 (7th September 2022) - Hampton, Debra; Hardin-Fanning, Fran; Hensley, Angie; Culp-Roche, Amanda; Wilson, Jessica L.; Thaxton-Wiggins, Amanda
Abstract: Assessing the resilience level of nursing faculty during a time of unprecedented change in nursing education was the focus of this study. A descriptive cross-sectional survey that incorporated demographic data and the 10-item Connor-Davidson Resilience Scale was used. Participants ( n = 78) had an average resilience score of 32.6. No correlation was found between resilience and demographic variables such as age, years of teaching experience, and type of nursing program. Resilience is important because it helps faculty assimilate various protective factors and persist during times of rapid change.